Enzymatic synthesis of new antimicrobial peptides for food purposes - Adaro, Mauricio; Ibáñez, Ángel Gabriel Salinas; Origone, Anabella Lucia; Vallés, Diego; Guzmán, Fanny; Vega, Alba; Barberis, Sonia (Frontiers in Microbiology, 2023)
In this study we report the enzymatic synthesis of N-α-[Carbobenzyloxy]-Ile-Gln (Z-IQ) which is the precursor of Ile-Gln (IQ), a new antibacterial dipeptide, using an aqueous–organic biphasic system formed by 50 % (v/v) ethyl acetate in 0.1 M Tris – HCl buffer pH 8. A partially purified proteolytic extract from the fruits of Solanum granuloso leprosum, named granulosain, proved to be a robust biocatalyst for the synthesis of Z-IQ, eliciting 71 ± 0.10 % maximal peptide yield in the above described conditions. After cleaving and purifying IQ dipeptide, antimicrobial activity was assayed against Staphylococcus aureus ATCC 25923, Staphylococcus hominis A17771 and Staphylococcus aureus C00195, and MIC values between 118 ± 0.01 μg/mL and 133.7 ± 0.05 μg/mL were obtained. In addition, IQ showed MIC of 82.4 ± 0.01 μg/mL and 85.0 ± 0.00 μg/mL against Escherichia coli ATCC 25922 and Escherichia coli A17683, respectively. IQ did not show inhibitory activity against simple resistant strains, such as Klebsiella oxytoca A19438 (SDR) and Pseudomonas aeruginosa C00213 (SDR), and against multidrug-resistant Enterococcus faecalis I00125 (MDR). IQ also caused growth inhibition of Helicobacter pylori NCTC 11638 and three wild-type H. pylori strains, which are sensitive to AML, MTZ, LEV and CLA (H. pylori 659), resistant to LEV (H. pylori 661 SDR), and resistant to MTZ (H. pylori 662 SDR). Finally, this study contributes with a new dipeptide (IQ) that can be used as an antimicrobial agent for food preservation or as a safe ingredient of functional foods.